Phrasemes in the Context of Students’ Communication - Dana Balakova; Viera Kovacova; Zdena Kralova (Communications - Scientific letters of the University of Zilina, 2007)
Phraseme application in all communication spheres and their appropriate performance forms are of particular interest to Slovak linguists against current dynamic tendencies in language communication. One of the necessary preconditions of successful communication is the knowledge and appropriate semantic interpretation of the most frequent phrasemes of a language. Since the language, culture and history are closely related, the phrasemes as specific lexical units reflecting life experience and wisdom of all generations help the language users in their overall personal advancement; including the phrasemes in the teaching of foreign languages is conditional on the differentiated level of language competence.